Settlement Analysis of Embankment on Piled Slab Segment - Andreanus Mooy Tambunan; Mohamad Khoiri; Mahendra Andiek Maulana (Interdisciplinary Social Studies, 2025)
Highway construction in Indonesia frequently encounters geotechnical problems due to soft soil conditions. The combination of pile slab construction and road embankments, which are commonly found on highways, has the potential for subsidence in the long term if 90% consolidation has not been achieved or primary settlement of the embankment has not been completed. This has the potential to disrupt the safety and serviceability of road users and cause delays in construction completion. Soft soil conditions, as found on the Patimban Subang Access Toll Road, have an NSPT value ?10 to a depth of 10 meters. This study aims to analyze the settlement of embankments using replacement and without replacement at the junction of the embankment segment and pile slab. By using a 1.5 m replacement in soft soil layers using the Terzaghi method, the cumulative settlement was 87.17 cm, while Plaxis 2D modeling showed a settlement of 93.90 cm. On the other hand, manual calculations without using replacement showed a cumulative settlement of 120.27 cm.